Activated LTB4 pathway in muscle tissue of patients with polymyositis or dermatomyositis. Issue 2 (26th June 2012) - Loell, Ingela; Alemo Munters, Li; Pandya, Jayesh; Zong, Mei; Alexanderson, Helene; Fasth, Andreas E; Ståhl Hallengren, Christina; Rådmark, Olof; Lundberg, Ingrid E; Jakobsson, Per-Johan; Korotkova, Marina
Objective: To investigate the involvement of the leukotriene B4 (LTB4) pathway in polymyositis (PM) and dermatomyositis (DM) and the effect of immunosuppressive treatment on the LTB4 pathway. Methods: 5-lipoxygenase (5-LO), 5-LO activating protein (FLAP) and LTB4 receptor-1 (BLT1) expression was analysed by immunohistochemistry in muscle tissue from patients with PM/DM before and after immunosuppressive treatment and from healthy individuals. In vivo LTB4 in thigh muscle was measured by microdialysis at rest and after acute exercise in another cohort of patients and healthy controls. Results: The number of 5-LO-positive cells and BLT1-positive capillaries was higher in patients with PM/DM than in healthy individuals. The number of FLAP-expressing cells divided the patients into two groups (high/low expression). Treatment reduced the number of FLAP-positive cells in the group with initial high levels, however the expression remained high compared with healthy individuals. The number of BLT1-positive cells was also reduced while staining for 5-LO was unchanged. An inverse correlation was observed between the number of 5-LO or FLAP-positive cells in muscle tissue and muscle performance. LTB4 could be detected in dialysate of muscle tissue in vivo in both patients and healthy controls and was significantly increased after exercise in patients. Conclusion: The LTB4 pathway is upregulated in muscle tissue from patients with PM/DM and this upregulation correlated negatively to muscle performance, suggesting a role for LTB4 in myositis muscle weakness. The immunosuppressive treatment was insufficient on the LTB4 pathway and, for patients with high expression of FLAP, FLAP inhibitors may be considered as possible therapy.